Rediscovering grounded theory - Gibson, Barry (SAGE Publications, Inc, 2014)
Rediscovering Grounded Theory is a bold re-evaluation of the origins of grounded theory, a philosophical clarification of its key ideas and a presentation of the most effective way to use its techniques in your research. It answers questions such as 'What should grounded theory look like?', 'How do I recognise grounded theory?' and 'How do I produce good grounded theory?' by returning to the original ideas as they were presented by Glaser and Strauss.